EVALUASI PENGELOLAAN DANA DESA DI DESA KALASEY DUA KECAMATAN MANDOLANG KABUPATEN MINAHASA - Tita Natalia Kaluntas; Olly Esry Harryani Laoh; Yolanda Pinky Ivanna Rori (AGRI-SOSIOEKONOMI, 2019)
This study aims to evaluate Village Fund management in Kalasey Dua illage, Mandolang Sub-district, Minahasa Regency. The study was conducted from May 2018 to January 2019. The data used in this study were primary data and secondary data. Primary data was collected based on interviews with two members of the Village Consultation Board (BPD), three village officials, and 50 community members to find out their responses to Village Fund management. The fifty community members were selected community members that have over the age of 21 years and had lived in the research village for more than 10 years. So the total respondents were 55 people.Interviews with community members were used by Likert Scale. Secondary data in this study came from the archives and reports of Kalasey Dua Village office in the form of Village Monographs, Village Fund Management Data andother documents relating to the management of the Kalasey Dua Village Village Fund; and through books available at local bookstores; and the internet. Internet used google searching to access articles from various scientific journals and theses from other universities related to the topic of this research. Data analysis using descriptive analysis. The results of the study indicate that overall the Village Funds received in Kalasey Dua Village have been managed properly by the government or the management, both in the management procedure with the availability of documents; and adhere to the principles of village fund management that consists of justice, needs, village authority, participation, self-management and village-based resources, village typology, transparency and accountability; and the community have felt the benefits. The Village Fund has been giving benefit to community of the village, both in the construction of infrastructure (roads, culverts, solar street lighting) and the empowerment of rural communities (by technical guidance of the management of Village-Owned Enterprises or BUMDES outside the region).*gmhk+erprm*